EUV spectroscopy of optically thin Ge VI-XI plasmas in the 9-18 nm region. (September 2019) - Maguire, O.; Kos, D.; O'Sullivan, G.; Sokell, E.
Highlights: Identification of new transition lines of germanium. Valence to sub-valence transition intensity ratios. Comparison between an optically thick and an optically thin spectra. CO2 pulse length shaping. Comparison between collisional radiative and coronal equilibrium models. Abstract: Identification of previously unclassified emission features in the extreme ultraviolet (EUV) spectra of Ge VI to XI has been carried out by recording emission from laser-produced plasmas created using a high-powered Transversely Excited Atmospheric (TEA) CO2 laser. The analysis was carried out using the Cowan suite of atomic structure codes with the aid of the unresolved transition array (UTA) statistical approach to determine the extent of the transition arrays, lines in Ge VI to Ge XI have been identified.